Determinants of household contributions to collective irrigation management: the case of the Doho Rice Scheme in Uganda - Nakano, Yuko; Otsuka, Keijiro (Cambridge University Press, 2011)
In order to explore the conditions for successful communal irrigation management, this study investigates the determinants of household contributions to the cleaning of irrigation channels and the availability of water. By using household-level data collected in a large-scale gravity irrigation scheme in Uganda, whose management was transferred from the government to the community, we find that household contributions to the cleaning of irrigation channels are determined by the scarcity of irrigation water, the opportunity cost of labor and the private benefit associated with plot size. We also find that the availability of irrigation water increases in the tertiary irrigation canal where the coefficient of variation of plot size is large, which may indicate that farmers of larger plots are particularly active in water management. These findings suggest that farmers are responsive to private benefits and, hence, the support of the government for communities to implement punishment may be effective for successful irrigation management.